Leadership and Organizational Culture Favorable to the Success of Modern Organization Development : A Case Study of Metropolitan Operating Line of Thai Postage Company - Woraphatthirakun, Phapassorn (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The objectives of the study are founded : 1) to determine the leadership and organizational culture favorable to the success of modern organization development in the Metropolitical Operating line of Thai Postage Company Limited ; 2) to compare the employees’ personal backgrounds in relation to leadership and organizational culture ; 3) to ascertain the relationship between leadership plus organizational culture and the success of modern organization development ; and 4) to find out problems and obstacles together with recommendations pertaining to leadership and or organizational culture conducive to the success of modern organization development in the case of the Metropolitan Operating line of Thai Postage Company Limited by 400 employees working in the Metropolitan Operating line comprised the sample for the study ; the sample size was determined by Yamane’s formula. The study instruments were a set of self-administered questionnaires and a semi - structured interview guide; the construction of these data - collecting tools was based on theory, conceptual framework and operational definitions Research findings are concluded as follows: 1. Leadership and organizational culture leading to the success of modern organization development was free-rein or nondirective leadership, the mean score being the highest (X = 3.55), followed by trans formational leadership (X = 3.49) ; meanwhile, exchange-oriented leadership had the least mean score (X = 3.53). As far as the organizational culture factors were concerned, the factors in descending order by strength or degree were as follows: self-adjustment dimension (X = 3.60), mission dimension (X = 3.53), unity dimension (X = 3.56), and participation dimension (X = 3.54). 2. As for the relationship between the employees’ personal backgrounds and leadership plus organizational culture, they failed to differ at the statistical significance level of .05. Regarding the relationship between the leadership style and the success of modern organization development, the researcher has found the following facts : transformational leadership had a high, positive correlation with the success of modern organization development (r = .843) ; exchange-oriented leadership had a moderate, positive correlation with the success of modern organization development (r = 445) ; and finally, free-rein leadership had a low, positive correlation with the success of modern organization development (r = 685). In view of the organizational culture and its relationship to the success of modern organization development, the researcher has formal the following : “participation dimension” was positively correlated with the success of modern organization development (r = 633). “mission dimension” was positively correlated with the success of modern organization development (r = 494). “unity dimension” was positively correlated with the success of modern organization development (r = 392) ; and “self-adjustment dimension” was positively correlated with the success of modern organization development (X = .268). As a result of multiple regression analysis, it was found that 83% of the success of modern organization development in the case of Thai Postage Company Limited. (Metropolitan Operating Line) was explained by the leadership factors, whereas 81% of the success of modern development organization development was explained by organizational culture factors. Article history : Accepted 7 May 2015 SIMILARITY INDEX = 2.88